1987
DOI: 10.1021/ja00243a010
|View full text |Cite
|
Sign up to set email alerts
|

Configurational statistics of acyl chains in polyunsaturated lipid bilayers from deuterium NMR

Abstract: To gain a better understanding of the biological roles of polyunsaturated phospholipids, deuterium (2H) NMR studies have been conducted of 1 -perdeuteriopalmitoyl-2-docosahexaenoyl-sn-glycero-3-phosphocholine, an asymmetric or mixed-chain saturated-polyunsaturated phospholipid, in the liquid crystalline (La) phase. The palmitoyl (16:O) chain at the glycerol sn-1 position was labeled with 2H by perdeuteration, whereas the polyunsaturated, docosahexaenoyl (22:6w3) chain at the sn-2 position was unlabeled, Le., p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
2

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(153 citation statements)
references
References 5 publications
10
141
2
Order By: Relevance
“…While the thermal properties of the Lp to La transition are similar for ether-and ester-linked phospholipids, ether lipids exhibit polymorphisms in the gel state, including the formation of interdigitated phases (41,42). It has also been suggested from 2H NMR studies that 1-palmitoyl, 2-docosahexaenoyl phosphatidylcholine may form interdigitated phases in the La state (43).…”
Section: Discussionmentioning
confidence: 99%
“…While the thermal properties of the Lp to La transition are similar for ether-and ester-linked phospholipids, ether lipids exhibit polymorphisms in the gel state, including the formation of interdigitated phases (41,42). It has also been suggested from 2H NMR studies that 1-palmitoyl, 2-docosahexaenoyl phosphatidylcholine may form interdigitated phases in the La state (43).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that the presence of Chol in a membrane, including reconstituted membranes containing the nAChR (7), leads to an ordering of the fatty acyl chains and thus a decrease in fluidity (20). Although the effects of DOPA on the physical properties of EPC membranes are not well characterized, it is possible that the very small head group leads to a lateral condensation of the lipid acyl chains and thus an increased ordering of the lipid bilayer (21,22). In support of the latter, it has been shown that increasing levels of DOPA in reconstituted EPC membranes lead to a decrease in the proportion of lipid ester carbonyls that are hydrogen-bonded to water, which could correspond to a decreased penetration of water into the lipid head group region of the bilayer as a result of a lateral condensation of the phospholipids (23).…”
Section: CMmentioning
confidence: 99%
“…Chol has a well characterized ordering effect on lipid bilayers in the liquid-crystalline state. The very small head group of DOPA should lead to a condensation and thus a restriction in the amplitudes of motion of the fatty acyl chains and thus a more ordered, less fluid lipid bilayer (26,27). The presence of both lipids could lead to a relatively ordered lipid membrane that might be required for maintaining the nAChR in a predominantly resting conformation.…”
mentioning
confidence: 99%